ANALISIS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN DALAM MODEL PEMBELAJARAN DEMONSTRASI PADA MATERI PEMBUATAN BATU BETON - Desti Intan Andini (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This study aims to analyze the use of learning videos in the material of the process of making concrete stones to increase the understanding of student literacy in the world of education. Using the systematic literature review (SLR) method, researchers collect data from previous research by analyzing and recapitulating research results in terms of the effectiveness of the media and learning models used. The results of the analysis in this study that are in accordance with the data obtained draw conclusions that the learning video media in the demonstration learning model in the subject of making concrete stones, helps increase students' understanding in understanding the procedures or steps of the process of making concrete stones.